2018
DOI: 10.21608/ajfm.2018.18202
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Various Scoring Systems in Prediction of Acute Aluminum Phosphide (ALP) Poisoning Outcome

Abstract: Introduction: Aluminum phosphide (Alp) poisoning is a major health problem developing countries because of the high rates of morbidity and mortality even in well-equipped and experienced hospitals.. The aim of this study: Was to evaluate various scoring system (Acute Physiology and Chronic Health Evaluation (APACHE) score, Rapid Emergency Medicine Score (REMS), The Sequential Organ Failure Assessment (SOFA) score) at admission for outcome prediction in acute aluminum phosphide poisoned patients. Patients and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 28 publications
(37 reference statements)
3
10
0
Order By: Relevance
“…Similarly, Shadnia et al (2010) found that respiratory rate ranged from 0 to 55 cycles/min in acute aluminum phosphide poisoned patients who were admitted to ICU. Tachypnea could be a sign of metabolic acidosis which was the most common type of acid base disturbance in the current study (Abd Elghany et al, 2018).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Similarly, Shadnia et al (2010) found that respiratory rate ranged from 0 to 55 cycles/min in acute aluminum phosphide poisoned patients who were admitted to ICU. Tachypnea could be a sign of metabolic acidosis which was the most common type of acid base disturbance in the current study (Abd Elghany et al, 2018).…”
Section: Discussionmentioning
confidence: 55%
“…As regard outcome of acute aluminum phosphide poisoned cases, all cases that needed ICU were in need for vasopressors and 91.1% of them died. This could be explained by the highly cardiotoxic property of aluminum phosphide without specific antidote (Abd Elghany et al, 2018). Moreover, aluminum phosphide leads to refractory hypotension which doesn't respond to crystalloid administration and the second step in management is administration of vasopressors (Farahani et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This short delay time could be explained by the presence of TUPCC in the center of Delta region with readily available transportations. Furthermore, a large number of the cases who attempt suicide are just trying to gain sympathy and draw attention of their beloved ones and not aiming to end their lives, therefore, they seek medical advice rapidly (Abd Elghany et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Intensive care admission for the need of mechanical ventilation is frequently required in ALP poisoning due to hypoxia, adult respiratory distress syndrome, and disturbed conscious level (Abd Elghany et al 2018;Louriz et al 2009;Mehrpour et al 2008). Definitely, the favorable effects of ILE in this regard minimize costs, efforts, and the complications related to ventilation.…”
Section: Discussionmentioning
confidence: 99%